The Effectiveness of Dialectical Behavior Therapy on Psychological Resilience and Existential Anxiety in Adolescents with Leukemia - Ebrahim Rahbar Karbasdehi; Abbas Ali Hosseinkhanzadeh; Fatemeh Rahbar Karbasdehi (Shiraz University of Medical Sciences, 2021)
Background: Adolescents with leukemia experience a variety of physical and psychological stresses that affect their quality of life. Given the association of resilience and existential anxiety with cancer, one of the methods to help adolescents with leukemia is through dialectical behavior therapy (DBT). The present study aimed to determine the effectiveness of DBT on psychological resilience and existential anxiety in adolescents with leukemia. Methods: This quasi-experimental study included a pretest / posttest design and a control group. The study sample consisted of 38 adolescents with leukemia living in Rasht City, Guilan Province, Iran (2019); the participants were selected by a simple random sampling and were randomized into an experimental and a control group. Connor-Davidson Resilience Scale (CD-RISC) and Existential Anxiety Inventory (EAI) were used for data collection before and after the intervention. A 12-session DBT was performed for the experimental group, but the control group received no treatment. The analysis of covariance (ANCOVA) was used for data analysis. Results: The mean ± standard deviation (SD) of the post-test scores for personal competence, strengthening effect of stress, positive acceptance of change, perceptions of control, spiritual influences, and existential anxiety were respectively 29.83 ± 2.28, 24.47 ± 2.51, 17.58 ± 2.19, 10.82 ± 2.47, 6.96 ± 2.14, and 11.75 ± 2.65 in the experimental group and 13.81 ± 2.31, 12.61 ± 2.84, 9.97 ± 2.45, 4.28 ± 1.66, 3.74 ± 1.19, and 22.31 ± 2.23 in the control group. The results indicated that the DBT improved the psychological resilience and existential anxiety in adolescents with leukemia (p <0.001). Conclusions: DBT can be an appropriate therapy for reducing the anxiety in adolescents with leukemia and increasing the resilience in people with chronic diseases; it can also result in life satisfaction among adolescents. This research confirms the fundamental importance of the above facts for education and mental health of adolescents.